2002
DOI: 10.1152/ajpgi.00117.2001
|View full text |Cite
|
Sign up to set email alerts
|

Gastrin stimulates the growth of gastric pit cell precursors by inducing its own receptors

Abstract: .-Gastrin/CCK-B receptors (CCKB-Rs) are present on parietal and enterochromaffin-like cells in the gastric mucosa but not on pit cells in the proliferative zone. Because serum gastrin levels are well correlated with the growth of the gastric pit, we examined whether pit precursor cells express CCKB-Rs using hypergastrinemic transgenic mice and a mouse pit precursor cell line, GSM06. In situ hybridization indicated that CCKB-R mRNA was limited to the lower one-third of the mucosa in control mice, whereas it was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
36
0
1

Year Published

2002
2002
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(40 citation statements)
references
References 49 publications
(63 reference statements)
3
36
0
1
Order By: Relevance
“…In a transgenic mouse model of hypergastrinaemia in which there is a gastric hyperproliferative condition, there is reported to be induction of the CCK-2 receptor on proliferating cells [80]. Moreover, there is now evidence for rapid, specific, increases in expression at the margin of cryoulcers induced in rat stomach [104].…”
Section: Control Of Expression Of the Cck-2 Receptormentioning
confidence: 99%
“…In a transgenic mouse model of hypergastrinaemia in which there is a gastric hyperproliferative condition, there is reported to be induction of the CCK-2 receptor on proliferating cells [80]. Moreover, there is now evidence for rapid, specific, increases in expression at the margin of cryoulcers induced in rat stomach [104].…”
Section: Control Of Expression Of the Cck-2 Receptormentioning
confidence: 99%
“…Moreover, Hirayama et al (1999) have shown that poorly differentiated adenocarcinomas as well as carcinoid tumors develop during H. pylori-induced gastritis with hypergastrinemia. Recent studies have shown that gastrin receptors are present on gastric mucosal progenitor cells, suggesting that gastrin has direct trophic actions on gastric mucosal cells (Kazumori et al, 2001;Nakajima et al, 2002). On the other hand, several investigators have reported that gastrin promotes gastric mucosal cell proliferation indirectly by stimulating the production of growth factors such as TGF-␣, heparinbinding epidermal growth factor-like growth factor, and Reg (Fukui et al, 1998;Miyazaki et al, 1999;Wang et al, 2000).…”
Section: Fukui Et Almentioning
confidence: 99%
“…Recent studies have shown that the biological action of gastrin is mediated by its receptor, gastrin/CCKB receptor (Nakajima et al 2002). Gastrin possesses the same five amino acids on its carboxyl terminal end as cholecystokinin (CCK).…”
Section: Introductionmentioning
confidence: 99%